DZIEDZICTWO FILMOWE W PRAWIE UNII EUROPEJSKIEJ - Kakareko, Ksenia (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Film heritage is an ever-expanding group of materials. Unfortunately, they do not have uniform regulations for their collection, maintenance and sharing. This article shows the course of work on subsequent European Union documents regulating issues related to film and audiovisual works. This article presents the standards developed by the European Union concerning the consistency of methods of collection, maintenance and interoperability of databases containing audiovisual works.